PMO-123 Gene transfer of dimethylarginine dimethylaminohydrolase-1 reduces portal pressure in a rodent model of cirrhosis. (28th May 2012) - Mehta, G; Sharma, V; Habtesion, A; Balasubramaniyan, V; Davies, N A; Jalan, R; Budhram-Mahadeo, V; Mookerjee, R P
Abstract : Introduction: Portal hypertensive bleeding is a grave complication of cirrhosis. Asymmetric dimethylarginine (ADMA), an endogenous eNOS inhibitor, is elevated in cirrhosis, relates to degree of portal hypertension, and is prognostic in acute-on-chronic liver failure. Dimethylarginine-dimethylaminohydrolase-1 (DDAH-1), a key enzyme metabolising hepatic ADMA, is reduced in cirrhosis. Therapies which indirectly increase hepatic DDAH-1, such as anti-TNFα therapy or FXR agonists, lead to reduced hepatic ADMA, increased NO and lowered portal pressure. Therefore, there is accumulating evidence for DDAH-1 as a therapeutic target, but specific evidence for DDAH-1 reconstitution is lacking. The aim of this study was to adopt a DDAH-1 gene therapy strategy in portal hypertension. Methods: Hydrodynamic injection leads to hepatic gene transduction by causing turbulent, retrograde venous flow, permeation of hepatic parenchymal cells and consequent plasmid expression. Human DDAH-1 cDNA was cloned into the pCMV-Sport6 expression plasmid. Sprague-dawley rats (n=9) underwent bile duct-ligation, and after 4 weeks were injected with 800 μg of either pCMV-Sport6-DDAH1 (n=5) or non-expressing control plasmid (n=4). After 72 h, rats underwent direct portal pressure assessment under anaesthesia and were then sacrificed. Plasma ALT was measured by Cobas-Integra analyser. Transgene expression was measured by quantitative PCR, with Taqman probes specific for human DDAH-1 to distinguish rodent DDAH-1. Protein expression was measured by western blot. Results: Highly effective gene transfer (between 20 and 120-fold increase) of human DDAH-1 was seen in 3 out of 5 treated animals. None of the animals treated with control plasmid expressed human DDAH-1. The three "responders" to gene therapy also had highly significantly increased DDAH-1 protein expression compared with "non-responders" or controls (p<0.05). There was no difference in ALT between the groups. Portal pressure was significantly lower in "responders" to gene therapy than "non-responders" or animals treated with control plasmid (p<0.05). Conclusion: This study demonstrates that DDAH-1 is a specific molecular target for portal pressure reduction. Hydrodynamic injection is variable in efficiency of gene delivery due to the nature of the technique. However, despite these limitations, this study clearly shows proof of concept for efficient vector-based DDAH-1 gene therapy in lowering portal pressure and preventing bleeding in cirrhosis. Competing interests: None declared.